2016
DOI: 10.1097/mao.0000000000001134
|View full text |Cite
|
Sign up to set email alerts
|

Serial Monitoring of Otoacoustic Emissions in Clinical Trials

Abstract: The purpose of this report is to provide guidance on the use of otoacoustic emissions (OAEs) as a clinical trial outcome measure for pharmaceutical interventions developed to prevent acquired hearing loss secondary to cochlear insult. OAEs are a rapid, noninvasive measure that can be used to monitor cochlear outer hair cell function. Serial monitoring of OAEs is most clearly established for use in hearing conservation and ototoxicity monitoring programs in which they exhibit more frequent and earlier changes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…Because basal regions of the cochlea are the most susceptible to damage, OAE changes are often first observed and most prominent at high frequencies. Unfortunately, the clinical application of these findings has been hampered by large test-retest differences across measurement sessions, differences that are particularly acute at high frequencies (reviewed in Konrad-Martin et al, 2016). Here, we show that the repeatability of OAE measurements can be substantially improved by correcting for the effects of ear-canal acoustics (e.g., standing waves) on both the evoking sound stimulus and the resulting OAE pressures.…”
Section: Introductionmentioning
confidence: 65%
“…Because basal regions of the cochlea are the most susceptible to damage, OAE changes are often first observed and most prominent at high frequencies. Unfortunately, the clinical application of these findings has been hampered by large test-retest differences across measurement sessions, differences that are particularly acute at high frequencies (reviewed in Konrad-Martin et al, 2016). Here, we show that the repeatability of OAE measurements can be substantially improved by correcting for the effects of ear-canal acoustics (e.g., standing waves) on both the evoking sound stimulus and the resulting OAE pressures.…”
Section: Introductionmentioning
confidence: 65%
“…DPOAE measurements have long been employed in clinical practice to distinguish between normal and impaired hearing, and more specifically, cochlear function (e.g., [25]). DPOAEs have been leveraged for ototoxic monitoring approaches such that DPOAE measurements consistently demonstrate earlier signs of ototoxic damage at the same frequencies when compared to conventional (1-8 kHz) behavioral hearing thresholds (e.g., [2,7,26]). It has also been demonstrated that higher frequency (>8 kHz) information is most valuable for timely detection of cochlear dysfunction and specifically utilizing high-frequency DPOAEs [16,27].…”
Section: Advancing Distortion Product Otoacoustic Emission (Dpoae) Pamentioning
confidence: 99%
“…This basal cochlear damage manifests as high-frequency hearing loss, which can be mitigated and/or management solutions adopted to optimize quality of life for patients if detected in a timely manner. Emerging research in the realm of otoprotectants and otorescue agents are further highlighting the need to establish methods for characterizing and monitoring cochlear health (e.g., [2]). Moreover, distortion product otoacoustic emissions (DPOAEs) offer a noninvasive, objective approach to monitor cochlear health utilizing frequencies and paradigms beyond those traditionally tested in patients unable to respond via conventional methods.…”
Section: Introductionmentioning
confidence: 99%
“…Greater variability is reported for higher frequency measurements where a change of 2.3 to 8 dB constituted a significant change for frequencies of 6-7 kHz [38,39]. To increase the accuracy for estimating DPOAE short-term test-retest change expectations, a meta-analysis including data from 10 published studies was completed [40]. The 90% reference limit for DPOAE test-retest changes ranged from ±3.76 to ±5.63 dB for f 2 frequencies spanning 1 to 6 kHz.…”
Section: Introductionmentioning
confidence: 99%
“…DPOAE testing is used in serial monitoring programs due to its objective, quick, frequency-specific, and repeatable nature [40][41][42][43][44][45][46], but testing is restricted to frequencies ≤10 kHz due to a lack of commercially available equipment able to reliably produce stimulus tones >10 kHz. Ideally, cochlear health would be monitored at the highest frequencies producing a response as this is where damage initially occurs due to ototoxic drug exposures [47].…”
Section: Introductionmentioning
confidence: 99%